2016
DOI: 10.1186/s13071-016-1639-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to vector-borne pathogens in candidate blood donor and free-roaming dogs of northeast Italy

Abstract: BackgroundMany vector-borne pathogens including viruses, bacteria, protozoa and nematodes occur in northeast Italy, representing a potential threat to animal and human populations. Little information is available on the circulation of the above vector-borne pathogens in dogs. This work aims to (i) assess exposure to and circulation of pathogens transmitted to dogs in northeast Italy by ticks, sandflies, and mosquitoes, and (ii) drive blood donor screening at the newly established canine blood bank of the Istit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 60 publications
2
29
2
Order By: Relevance
“…In conclusion, it is here shown that regular investigations should be encouraged in areas where data on parasite occurrence is still limited, and that prompt diagnosis and infection control are a prority. This is especially relevant for Mediterranean countries where epizootiological and biological conditions favour the occurrence and circulation of several parasitoses and VBDs in animal populations due to good and animal trade, dog adoptions and holiday trips of people [36, 43, 6163]. As visitors and tourists often bring their pets during holidays, introduction of parasites from endemic to free areas can occur.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, it is here shown that regular investigations should be encouraged in areas where data on parasite occurrence is still limited, and that prompt diagnosis and infection control are a prority. This is especially relevant for Mediterranean countries where epizootiological and biological conditions favour the occurrence and circulation of several parasitoses and VBDs in animal populations due to good and animal trade, dog adoptions and holiday trips of people [36, 43, 6163]. As visitors and tourists often bring their pets during holidays, introduction of parasites from endemic to free areas can occur.…”
Section: Resultsmentioning
confidence: 99%
“…Ticks are important vectors for diseases and their global distribution contributes to the increase of emerging and re-emerging tick-borne diseases world-wide (Jongejan and Uilenberg 2004, Cutler 2010, Guglielmone et al 2013, de la Fuente et al 2017. The prevalence of vector-borne diseases in a population closely reflects the distribution and density of vectors (Aktas et al 2015, Vascellari et al 2016.…”
mentioning
confidence: 99%
“…[45]. Previous studies report A. phagocytophilum in ticks of domestic dogs and wild carnivores from Italy, with a prevalence ranging from 0% to 16.6% [22,[46][47][48][49][50][51][52][53][54]. A. platys and E. canis were reported in tick pools from both northern and southern provinces (p>0.05), in contrast with previous reports of higher seroprevalence levels in dogs from southern Italy [54,55] and Sardinia [56].…”
Section: Discussionmentioning
confidence: 73%